Teaching Translation & developing student’s skill: Theories and Methods - Chenni, Fairouz (Journal of Human Sciences, 2021)
Translation is very closely related to linguistic studies; because, each current of language theory corresponds to a translation theory. For teaching Translation, the application of different theories and methods of translation and language is compulsory for learning transmission strategies during translation. So, how to apply these theories and methods during the translation study in order to develop student’s skills?